2017
DOI: 10.1017/s1368980017002191
|View full text |Cite
|
Sign up to set email alerts
|

Maternal pre-pregnancy BMI and offspring body composition in young adulthood: the modifying role of offspring sex and birth order

Abstract: A higher pre-pregnancy BMI was associated with higher offspring %FM and lower offspring %LM in late adolescence and young adulthood, with stronger associations for first-born daughters. Preventing obesity at the start of women's reproductive life might reduce the risk of obesity in her offspring, particularly for daughters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 32 publications
(49 reference statements)
2
32
1
Order By: Relevance
“…Human model studies show that maternal anthropometrics and BMI (body mass index) influence offspring development (49, 50). For example, Chaparro et al (11) reported that a high maternal pre-pregnancy BMI was associated with a higher offspring percentage of fat-mass and, therefore lower percentage of lean mass. In the current study, we did not measure maternal anthropometrics either prior to– or during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Human model studies show that maternal anthropometrics and BMI (body mass index) influence offspring development (49, 50). For example, Chaparro et al (11) reported that a high maternal pre-pregnancy BMI was associated with a higher offspring percentage of fat-mass and, therefore lower percentage of lean mass. In the current study, we did not measure maternal anthropometrics either prior to– or during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The direct association between maternal pre-pregnancy BMI and offspring adiposity agreed with previous studies that also assessed body composition using indirect methods, such as DXA and air-displacement plethysmography in childhood (4)(5)(6)(7)28) . We found three studies assessing offspring adiposity in adulthood, but only one considered maternal pre-pregnancy BMI (8) , while the others assessed maternal weight at early or late pregnancy (13,29) . One of them was conducted with 276 adults in Scotland whose skinfold-estimated body fatness was predicted by maternal early pregnancy BMI (13) .…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 99%
“…As far as the offspring is concerned, maternal prepregnancy BMI was shown to be associated with adiposity later in life, resulting in a 'vicious cycle of obesity' (4)(5)(6)(7)(8) . Genetic components could partly explain this association (9) , but it is known that epigenetic mechanisms, through metabolic programming during the first 1000 d of life, play an important role on this issue (10,11) .…”
mentioning
confidence: 99%
See 2 more Smart Citations